2012
DOI: 10.1093/bja/aer305
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety and pain sensitivity are independent predictors of propofol and sevoflurane requirements in general anaesthesia

Abstract: Preoperative anxiety and pain sensitivity are independent predictors of propofol and sevoflurane requirements in general anaesthesia. Anaesthetic and analgesic doses could be modified based on the patient's preoperative anxiety and pain sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 28 publications
(16 reference statements)
3
92
1
6
Order By: Relevance
“…But the state anxiety (STAI-S), measured both in the waiting room ( Figure 2) and in the operating room just before induction (Figure 3), had no significant positive correlation with the Propofol dose requirement. This is in agreement with previous studies of Marantes et al 5 and Kil et al 6 On the other hand, heart rate (HR), which was measured in the operating room just before the induction (Figure 4), had strong positive correlation with the Propofol dose requirement for induction. We also observed that STAI-S measured in the operating room had a strong positive correlation with HR ( Figure 5).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…But the state anxiety (STAI-S), measured both in the waiting room ( Figure 2) and in the operating room just before induction (Figure 3), had no significant positive correlation with the Propofol dose requirement. This is in agreement with previous studies of Marantes et al 5 and Kil et al 6 On the other hand, heart rate (HR), which was measured in the operating room just before the induction (Figure 4), had strong positive correlation with the Propofol dose requirement for induction. We also observed that STAI-S measured in the operating room had a strong positive correlation with HR ( Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…5 Kil et al reported that, during the induction of anesthesia, patients with higher levels of both state and trait anxieties required greater amounts of propofol to reach light (85) and moderate levels (75) of sedation. 6 However, the amount of Propofol required to reach a deep level of sedation (BIS 65), was associated with higher levels of trait, but not state anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Preoperative anxiety and pain sensitivity have been shown to be independent predictors of propofol and sevoflurane requirements in general anesthesia as well as risk factors for poor pain control in the postoperative period. 6 The most important predictor of postoperative pain in ambulatory surgery is the presence of preoperative pain. Other factors that may also impact anesthesiologists' care include the anticipated degree of postoperative pain and the patient's high preoperative expectations regarding postoperative analgesia.…”
Section: Preoperative Pain Anxiety and Catastrophizingmentioning
confidence: 99%
“…5 Il a été démontré que l'anxiété préopératoire et la sensibilité à la douleur étaient des prédicteurs indépendants de besoins élevés en propofol et en sévoflurane durant l'anesthésie générale et constituaient des facteurs de risque de mauvais soulagement de la douleur en période postopératoire. 6 Le prédicteur le plus important de douleur postopératoire en chirurgie ambulatoire est la présence de douleur préopératoire. Parmi les autres facteurs pouvant également influencer les soins des anesthésiologistes, citons le degré anticipé de douleur postopératoire et les attentes préopératoires élevées du patient concernant l'analgésie postopératoire.…”
Section: Douleur Préopératoire Anxiété Et Catastrophisationunclassified